Effect of Freezing Process on the Microstructure of Gelatin Methacryloyl Hydrogels - Liu, Taotao; Zhang, Yuzhuo; Sun, Mingyue; Jin, Meiqi; Xia, Wei; Yang, Huazhe; Wang, Tianlin (Frontiers in Bioengineering and Biotechnology, 2021)
Gelatin methacryloyl (GelMA) hydrogels have aroused considerable interests in the field of tissue engineering due to tunable physical properties and cell response parameters. A number of works have studied the impact of GelMA concentration, photo-initiator concentration, methacrylic anhydride (MA) concentration, cooling rate and temperature gradient on GelMA hydrogel generation, but little attention has been paid to the effect of the freezing temperatures and freezing time of GelMA prepolymer solution during preparation. In this study, GelMA hydrogels were synthesized with different freezing temperatures and time. It was found that the lower freezing temperatures and longer freezing time caused smaller pore sizes that realized higher cell viability and proliferation of MC3T3-E1 cells. The results showed that tunable microstructure of GelMA could be achieved by regulating the freezing conditions of GelMA, which provided a broad prospect for the applications of GelMA hydrogels in tissue engineering.